2018
DOI: 10.1007/s00204-018-2302-0
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the incubation period in cytotoxicity testing with primary human hepatocytes

Abstract: Primary human hepatocytes (PHHs) remain the gold standard for in vitro testing in the field of pharmacology and toxicology. One crucial parameter influencing the results of in vitro tests is the incubation period with test compounds. It has been suggested that longer incubation periods may be critical for the prediction of repeated dose toxicity. However, a study that systematically analyzes the relationship between incubation period and cytotoxicity in PHHs is not available. To close this gap, 30 compounds we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Another question addressed in this study was how long cultivated hepatocytes should be exposed to test compounds, and whether repeated exposures are superior to a single addition of test compound (Gu et al 2018;Godoy et al 2013). Our results demonstrated that a two-day exposure period of the test compound (with only one addition of test compound at the morning after thawing and plating) lead to a higher TSI and TEI compared to 24 h or 7-day exposure with repeated culture medium changes containing fresh test compound.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Another question addressed in this study was how long cultivated hepatocytes should be exposed to test compounds, and whether repeated exposures are superior to a single addition of test compound (Gu et al 2018;Godoy et al 2013). Our results demonstrated that a two-day exposure period of the test compound (with only one addition of test compound at the morning after thawing and plating) lead to a higher TSI and TEI compared to 24 h or 7-day exposure with repeated culture medium changes containing fresh test compound.…”
Section: Discussionmentioning
confidence: 72%
“…In the present study, an incubation period of 48 h was used. Additionally, incubations of 24 h and 7 days (with repeated culture medium changes with fresh test compound) were performed as previously reported (Gu et al 2018). A higher TSI was obtained for the 48 h compared to the 24 h and 7 day incubation periods (Fig.…”
Section: In Vitro Test Optimization Based On Cytotoxicitymentioning
confidence: 85%
See 2 more Smart Citations
“…It remains open to which degree the transplanted human hepatocytes differ when transplanted into mouse livers compared to their state in the human microenvironment. A well-established alternative system to humanized mouse livers is cultivated human hepatocytes (Gu et al 2018;Deharde et al 2016;Reif et al 2015;Ghallab et al 2016;Kim et al 2015;Frey et al 2014), a cell system well established for the purpose of metabolite generation and identification (Hewitt et al 2007;Godoy et al 2013).…”
mentioning
confidence: 99%